Adolescencja jako fenomen psychospołeczny i grupa wiekowa we współczesnej przestrzeni społeczno-kulturowej i życiowej = Adolescence as a psycho-social phenomenon and an age-related group in the modern socio-cultural and living space - Šamne, Anželika V. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the analysis of the modern adolescence as a cultural and historical construct, a development period, a social and age-related group, as well as a psycho-social phenomenon. New trends of the psycho-social development of the present-day youth associated with a set of socio-cultural transformations of the late XX and the early ??? centuries have been examined. The features of the social conditions of the development of the present-day youth have been analysed in the context of M. Mead's ideas regarding the mutual substitution of post-figurative, co-figurative and pre-figurative cultures during the development of the mankind.
Keywords: chłopięctwo; subiekt kultury; przestrzeń społeczno-kulturowa; społeczna sytuacja rozwoju; cele wykształcenia; adolescence; subject of culture; socio-cultural space; social conditions of the development; education goals